1995
DOI: 10.1002/acp.2350090709
|View full text |Cite
|
Sign up to set email alerts
|

What goods can self‐assessment questionnaires deliver for cognitive gerontology?

Abstract: Donald Broadbent's work in developing and validating his Cognitive Failures Questionnaire (CFQ) incidentally contributed to our understanding of what self-assessment questionnaires (SAQs) can tell us about the nature of cognitive changes that occur in old age, and their effects on people's everyday lives. The literature on use of SAQs in age comparisons is reviewed in the context of this work, as is new empirical evidence that older people complain of general loss of memory efficiency but, paradoxically, repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 53 publications
3
40
0
Order By: Relevance
“…The absence of significant correlations between age and PRMQ scores is obviously in sharp contrast with age-related decline on objective laboratory tests of both prospective and retrospective memory (see reviews by Maylor, 1996, andZacks, 2000 respectively). Such age invariance in subjective memory ratings has been observed in many previous studies and has been attributed to several factors, notably the tendency to rate memory relative to one's peers (see Rabbitt, Maylor, McInnes, Bent, & Moore, 1995, for a summary of studies and detailed discussion). The present results would suggest that such factors apply to both prospective and retrospective items and therefore do not invalidate the main comparisons of interest as revealed by the modelling.…”
Section: Influence Of Demographic Variablesmentioning
confidence: 82%
“…The absence of significant correlations between age and PRMQ scores is obviously in sharp contrast with age-related decline on objective laboratory tests of both prospective and retrospective memory (see reviews by Maylor, 1996, andZacks, 2000 respectively). Such age invariance in subjective memory ratings has been observed in many previous studies and has been attributed to several factors, notably the tendency to rate memory relative to one's peers (see Rabbitt, Maylor, McInnes, Bent, & Moore, 1995, for a summary of studies and detailed discussion). The present results would suggest that such factors apply to both prospective and retrospective items and therefore do not invalidate the main comparisons of interest as revealed by the modelling.…”
Section: Influence Of Demographic Variablesmentioning
confidence: 82%
“…The CFQ has an internal validity of 0.91 and a test-retest reliability rate of 0.82 (Larson, Alderton, Neideffer, & Underhill, 1997). Self-report cognitive evaluation tests have been found to consistently reflect changes in cognitive processes, self-perception, as well as attitudes and adaptations to old age (Rabbit, Maylor, McInnes, Bent, & Moore, 2006).…”
Section: Instrumentationmentioning
confidence: 99%
“…These results are not unique: Gunzelmann et al [20], for instance, found that only the EOT and daydreaming subscales of the TAS-26 were subject to age effects, indicating that older adults daydream less and engage in more EOT. Self-reported daydreaming, for example, has been shown to decline considerably across the adult life span [49].…”
Section: A Refined Model Of Alexithymia?mentioning
confidence: 99%